Evaluating a virtual reality–delivered mindfulness intervention for anxiety: a mixed-methods study in real-world community and school settings - Rafiei, Sima; Santa, Kristof; Honey, Nicola; Tully, David; Mezes, Barbara (Frontiers in Psychiatry, 2025)
IntroductionAdolescent anxiety is rising globally, yet access to engaging mental health support remains limited, especially outside clinical care. Virtual reality (VR) offers a promising platform for delivering immersive mindfulness experiences. This study evaluated SpiritVR Journey, a six-session VR mindfulness programme designed for young people, delivered in real-world school and community environments.MethodsUsing an exploratory pre–post mixed-methods design, data were collected from 53 participants across schools, community organisations, and youth mental health services. Recruitment was facilitator-led and internal to each site. Quantitative data were gathered before and after each session using an adapted Generalised Anxiety Disorder scale (GAD-7), while qualitative reflections were obtained from participant diary entries. Sessions were delivered approximately once per week, depending on site scheduling.ResultsParticipants showed a significant reduction in self-reported anxiety symptoms across sessions (mean GAD-7 change = 4.88; Cohen’s d = 2.06). Qualitative themes highlighted relaxation, emotional relief, and improved self-regulation. The immersive format appeared particularly engaging for individuals who had found traditional mindfulness approaches challenging.DiscussionFindings provide preliminary evidence of impact and acceptability of immersive VR mindfulness in youth and community contexts. While results suggest promise for future scalable applications, broader feasibility depends on access to VR hardware, training of facilitators, and setting-specific implementation support.